2023
DOI: 10.1186/s12877-023-03950-x
|View full text |Cite
|
Sign up to set email alerts
|

Vision impairment, hearing impairment and functional Limitations of subjective cognitive decline: a population-based study

Abstract: Background The association between sensory impairment including vision impairment (VI), hearing impairment (HI), dual impairment (DI) and the functional limitations of SCD (SCD-related FL) are still unclear in middle-aged and older people. Methods 162,083 participants from BRFSS in 2019 to 2020 was used in this cross-sectional study. After adjusting the weights, multiple logistic regression was used to study the relationship between sensory impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…Therefore, good health services are needed for patients with VI and hearing loss to improve their health status and quality of life. At present, mental problems are a great global public health concern, and our study showed a 0.6-fold increased risk of psychological disorders in patients with VI, consistent with previous reports [ 40 , 41 ], which reminds the whole society and family to pay attention to the mental health of patients with VI.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, good health services are needed for patients with VI and hearing loss to improve their health status and quality of life. At present, mental problems are a great global public health concern, and our study showed a 0.6-fold increased risk of psychological disorders in patients with VI, consistent with previous reports [ 40 , 41 ], which reminds the whole society and family to pay attention to the mental health of patients with VI.…”
Section: Discussionsupporting
confidence: 92%
“…Cognitive decline is a well‐established predictor for the development of dementia. 16 Objective measures of sensory decline, such as visual acuity and auditory acuity, have been shown to be predictive of cognitive functioning cross‐sectionally 17 and up to 6 years later. 18 However, evidence suggests that subjective reports of sensory and cognitive impairment begin earlier than measurable differences in objective impairment such as cognitive scoring.…”
Section: Introductionmentioning
confidence: 99%